Characterization and antimicrobial activity of cellulose derivatives films incorporated with a resveratrol inclusion complex. (November 2016) - Silva, Ângela; Duarte, Andreia; Sousa, Sónia; Ramos, Ana; Domingues, Fernanda C.
Abstract: The aim of this study was to develop an active film based on cellulose derivatives (hydroxyethylcellulose and cellulose acetate), while using resveratrol and its inclusion complex with hydroxypropyl-γ-cyclodextrin as active agents. These films were prepared by the casting method. The structural, mechanical, barrier, surface free energy, optical and release properties were analyzed. The antimicrobial activity of these films against Campylobacter jejuni, Campylobacter coli and Arcobacter butzleri was evaluated by the agar diffusion method. The anti-quorum sensing (QS) activity of films was also studied using the biosensor strain Chromobacterium violaceum ATCC 12472. The active films developed in this work besides being transparent, inhibit the growth of the tested strain and had anti-QS activity. This study showed the potential of these active films as a new approach to control the growth of Campylobacter . Highlights: Cellulose bilayer films with resveratrol (RV) and inclusion complex (IC) were prepared. The addition of the antibacterials affected the physical properties of the films. Active bilayer films exhibited antimicrobial activity against Campylobacter . Active films with RV and IC inhibited the quorum sensing mechanism. RV and IC films have potential as bioactive packaging to improve food safety/quality.